PERANCANGAN ARSITEKTUR E-LEARNING DAN E-LIBRARY MENGGUNAKAN THE OPEN GROUP ARCHITECTURE FRAMEWORK- ARCHITECTURE DEVELOPMENT METHOD DI STKOM AL MA’SOEM BANDUNG - Tiffany Puspa Ramadhani (INTERNAL (Information System Journal), 2018)
The concept of digital learning or e-learning is now widely applied in many universities. in this research is done architecture design of e-learning information system equipped with e-library as storage media of material needed in learning and also as media of search of library material which amount is not limited. The background of this architectural design is two, which is less effective teaching and learning activities when there is holiday or lecturer absence and the last is the limited number of library  materials in hardcopy. E-learning and e-library as one of the impacts of information technology advances can be utilized to overcome the obstacles in STKOM Al Ma'soem. With e-learning lecturers can provide lectures without having to  face-to-face with students. Whereas with the use of e-library students can get library materials online without limited space and time.